Keratoconus: mechanisms of development (Ukrainian Journal of Ophthalmology, 2026)
To date, the problem of surgical treatment for keratoconus has not been solved completely. After corneal transplantation, high refractive errors (myopic astigmatism, as a rule) occur in a graft. This reduces visual outcomes of keratoplasty. Why is myopic refraction formed so persistently in the grafted cornea? Let us present our view of the problem.